Body, Meaning, Healing - Csordas, T. author. aut Link
IX, 321 p.
Keywords: Exactly where is the common ground between religion and medicine in phenomena described as 'religious healing?' In what sense is the human body a cultural phenomenon and not merely a biological entity? Drawing on over twenty years of research on topics ranging from Navajo and Catholic Charismatic ritual healing to the cultural and religious implications of virtual reality in biomedical technology, Body, Meaning, Healing sensitively examines these questions about human experience and the meaning of being human. In recognizing the way that the meaningfulness of our existence as bodily beings is sometimes created in the encounter between suffering and the sacred, these penetrating ethnographic studies elaborate an experimental understanding of the therapeutic process, and trace the outlines of a cultural phenomenology grounded in embodiment.